Processing mismatching gendered possessive pronouns in L1 Dutch and L2 French - Schoenmakers, Gert-Jan; Redl, Theresa; Collin, Sebastian; Versendaal, Rozanne; de Swart, Peter; de Hoop, Helen (Dutch Journal of Applied Linguistics, 2022)
The results of a self-paced reading experiment show that reading times in Dutch increase when there is a gender mismatch between the subject and a subsequent possessive pronoun, signaling an increase in processing difficulty. We hypothesized that Dutch learners of French incorrectly apply the rules of their L1 in their L2 and should therefore also show an increase in reading times in French upon encountering a possessive pronoun for which grammatical gender differs from the biological gender of the subject (the possessor). At the same time, we expected that they would have no or less difficulties in processing ungrammatical French sentences in which the biological gender of the subject/possessor matches the gender of the possessive pronoun. We did not find either of these effects in a second self-paced reading experiment. We assume that the Dutch learners of French parse the foreign language sentences in a shallow fashion.